Pengaruh Senam Tai Chi terhadap Peningkatan Kualitas Tidur Pada Lansia dengan Hipertensi - Devi Urbayanti, Putu; Sudiantara, Ketut; Mustika, I Wayan (Jurnal Gema Keperawatan, 2024)
Sleep disturbance or insomnia in the elderly is a condition where a person experiences changes in the quality and quantity of their sleep patterns which can cause discomfort in carrying out daily activities. Non-pharmacological therapy of Tai Chi exercises can be given to elderly people who experience sleep quality disorders. This study aims to determine the effect of Tai Chi exercises on improving the quality of sleep of elderly people with hypertension in the Kediri 1 Tabanan Health Center working area. This study used a quasy experiment design with the type of pre and post test with control group research using two groups, where one group was given Tai Chi exercise treatment and the control group was given conventional action in the form of elderly gymnastics. The number of respondents was 44 people with each group totaling 22 people taken by purposive sampling technique. The instrument used was the Pittsburgh Sleep Quality Index (PSQI) questionnaire. The results of non-parametric statistical tests with wilcoxon signed ranks test analysis in the treatment group were obtained p-value = 0,000 (p 0,05). The results of the posttest differential test between the treatment group and the control group tested using the mann-whitney u test showed a p-value of 0,002 (p 0,05), it can be concluded that there is a significant difference between the treatment group and the control group so that there is an effect of Tai Chi Gymnastics on improving sleep quality in elderly people with hypertension in the this Puskesmas working area.